Integrating Mathematical Analysis with Genomic Data for Predictive Health Modeling - Pasupuleti, Saichand; Boyapati, Phanindra sai (International Journal of Health Sciences, 2025)
Purpose: In today’s data-driven healthcare landscape, the ability to predict health outcomes with precision is no longer a distant goal—it’s an urgent necessity. This study explores how mathematical analysis, when combined with genomic data, can unlock powerful predictive models that help forecast diseases like cancer and genetic disorders. Our aim is to move healthcare from reactive treatment to proactive prevention, using the language of mathematics to decode the blueprint of life. Methodology: We adopted a rigorous, interdisciplinary approach that blends statistical modeling with machine learning. Genomic datasets were sourced from trusted repositories such as the 1000 Genomes Project and TCGA. Using tools like GATK, TensorFlow, and Scikit-learn, we built hybrid models—support vector machines, deep neural networks, and ensemble techniques—that can detect subtle genetic patterns. Bayesian probability was applied to estimate disease risk, and ethical safeguards were embedded throughout to ensure responsible data use. Findings: Our models demonstrated strong predictive accuracy, especially in identifying individuals at elevated risk for chronic conditions. Unique Contribution to Theory, Practice and Policy: The study contributes to both theory and practice by validating the use of ensemble learning and Bayesian inference in genomic prediction. In addition, it demonstrated how mathematical frameworks can personalize healthcare at scale. Lastly, it offered a replicable methodology for integrating bioinformatics with AI. This work stands as a bridge between abstract theory and clinical reality, showing how data science can directly improve patient care. To build on this foundation, the study recommended expanding models to include multi-omics data (e.g., proteomics, metabolomics) for a more complete health picture, enhancing computational infrastructure to support real-time clinical decision-making, strengthening ethical frameworks for genomic data sharing and consent and fostering deeper collaboration between researchers, clinicians, and policy-makers to accelerate adoption.